INCUBATORS AND GOVERNMENT POLICY FOR DEVELOPING IT INDUSTRY AND REGION IN EMERGING ECONOMIES - Mohd Fuaad Said,; Khairul Akmaliah Adham,; Nur Atiqah Abdullah,; Seppo Hänninen,; Steven T. Walsh, (Asian Academy of Management Journal, 2012)
Incubation, a concept supported by a variety of economic cluster theories, is a vital element in economic development in developed countries. The entrepreneurial businesses that they house often improve the developed economies in terms of not only jobs but also wealth creation. The question that this article embraces is as follows: "Do incubators play the same vital role in economic development in developing regions of the world?" We use the case study methodology to develop this query in a focus area of regional development in an emerging economy. We examine the implementation of three incubators located in designated cybercities. The cybercity concept is one of the Malaysian government's initiatives to encourage the development of the IT industry within the Multimedia Super Corridor (MSC) Program. This study takes advantage of the 10-year development of cybercities by performing a longitudinal study. We found that these incubators did well in achieving their initial performance objectives, but they need to catch up with developed countries' continued rapid progress.